A low noise flexible cable

By adopting the polytetrafluoroethylene film wrap sintering process and semiconductor layer design in the cable, combined with the method of adding magnesium hydroxide and flame retardant to the sheath material, the problems of cable noise and safety performance are solved, and the effects of low noise and high flame retardant and fire-resistant are achieved, which are suitable for scenarios such as 5G base stations.

CN115394479BActive Publication Date: 2025-04-08ANHUI LONGHANG ELECTRICAL EQUIP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211015990.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-24
Publication Date
2025-04-08
Estimated Expiration
2042-08-24

AI Technical Summary

Technical Problem

The existing cables are noisy under external factors such as bending, vibration, and temperature changes, which are difficult to meet the needs of micro signal measurements such as 5G base stations. At the same time, there are also shortcomings in safety performance.

Method used

High temperature-resistant polytetrafluoroethylene film and wrap-around sintering process are used to coat the outer wall of the conductor to form an insulating layer, and a semiconducting layer is formed between the braided shielding layer and the insulating interface. By adding magnesium hydroxide and flame retardant to the sheath material, the flame retardant and fire-retardant performance of the cable is improved.

Benefits of technology

It effectively reduces cable noise, improves flexibility, and meets the safety performance requirements of low smoke, halogen-free, flame retardant and fire-proof, and is suitable for 5G base stations and other scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003812527130000031
    Figure BDA0003812527130000031
  • Figure BDA0003812527130000041
    Figure BDA0003812527130000041
  • Figure BDA0003812527130000051
    Figure BDA0003812527130000051
Patent Text Reader

Abstract

The invention discloses a low-noise soft cable, which belongs to the field of cable technology, and comprises a conductor, an insulating layer, a braided shielding layer and a sheath layer arranged in sequence from the inside to the outside, wherein the conductor is formed by twisting copper wires, the insulating layer is coated on the outer wall of the conductor by wrapping and sintering, the surface of the insulating layer is coated with semi-conductive glue, the braided shielding layer is coated on the outside of the insulating layer and adhered to the outer wall of the insulating layer through the semi-conductive glue, and the sheath layer is coated on the outside of the braided shielding layer. The invention adopts a polytetrafluoroethylene film as an insulating layer, adopts a semi-insulating polycrystalline silicon material as a semi-conductive glue, and forms a semi-insulating polycrystalline silicon film after solidification, so as to achieve the effect of reducing noise; by adding magnesium hydroxide and a flame retardant to the outer sheath material, the sheath material is given a stable and lasting flame retardant effect; so that the obtained cable can simultaneously meet the requirements of low noise and fire retardancy, and has a wide range of application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cables, and in particular relates to a low-noise soft cable. Background Art

[0002] The influences on the cable come from both the outside and inside of the cable. The disturbance from the outside of the cable is called interference, and the disturbance from the inside of the cable due to physical reasons such as materials and structure is called noise. Metal shielding is usually used to suppress external interference of the cable, and the main reason for noise is the friction caused by the relative displacement between the internal insulation layer and the inner and outer conductors of the insulation layer when the cable is subjected to external forces (bending, vibration, etc.).

[0003] Low-noise cables are cables that generate pulse signals less than 5mV under the influence of external factors such as bending, vibration, impact, and temperature changes. Low-noise cables are mainly used for the measurement of tiny signals. When 5G base stations are running, there are interferences from external factors such as bending, vibration, temperature, and frequency changes, which makes low-noise cables have broad application prospects in the construction of 5G base stations. At the same time, the miniaturization and intensive coverage of 5G base stations are a major trend. Cables used in the core areas of computer rooms, some public places, and commercial areas must consider the safety performance of low smoke, halogen-free, flame retardant, and fireproof. Therefore, there is a broad prospect for the demand for low-smoke, halogen-free, flame retardant, fire-resistant, and low-noise cables. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a low-noise flexible cable.

[0005] The present invention adopts a high temperature resistant polytetrafluoroethylene film and a wrapping and sintering process to wrap the outer wall of the conductor to form an insulating layer. After wrapping and sintering, the polytetrafluoroethylene film can form a tight package with the conductor, making it difficult for the two to move relative to each other and separate, thereby reducing cable noise and making the cable more flexible. By adopting a semi-insulating polycrystalline silicon material as a semi-conductive glue, a semi-insulating polycrystalline silicon film is formed after solidification, which is a high temperature resistant film with semi-conductive characteristics. A semi-conductive layer is formed between the braided shielding layer and the insulating interface, which can achieve the effect of reducing noise.

[0006] The present invention adds magnesium hydroxide and a flame retardant to the outer sheath material at the same time. The flame retardant is a high-efficiency, multi-phase flame retardant component, and a small amount of addition can enable the material to obtain excellent flame retardant and fireproof effects. In addition, the flame retardant molecule also contains a terminal C=C, which can participate in the copolymerization process during the melt mixing process with the matrix material, thereby improving the interaction between the flame retardant and the matrix, thereby improving the stability of the flame retardant, improving the migration resistance and exudation resistance of the flame retardant, and giving the sheath material a stable and lasting flame retardant effect; thereby, the obtained cable meets the requirements of low noise and fire retardancy at the same time, and has broad application prospects.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A low-noise flexible cable comprises a conductor, an insulating layer, a braided shielding layer and a sheath layer which are sequentially arranged from the inside to the outside;

[0009] The conductor is made of twisted copper wires, the insulating layer is coated on the outer wall of the conductor by wrapping and sintering, the surface of the insulating layer is coated with semi-conductive glue, the braided shielding layer is coated on the outside of the insulating layer and adhered to the outer wall of the insulating layer through the semi-conductive glue, and the sheath layer is coated on the outside of the braided shielding layer.

[0010] Furthermore, the insulating layer adopts high temperature resistant polytetrafluoroethylene (PTFE) film, and is wrapped around the outer wall of the conductor by a wrapping and sintering process. After wrapping and sintering, the polytetrafluoroethylene film can form a tight package with the conductor, making it difficult for relative movement and separation between the two, thereby reducing cable noise and making the cable softer.

[0011] Furthermore, the semi-conductive adhesive uses a semi-insulating polysilicon material, which forms a semi-insulating polysilicon film after curing. The film is a high-temperature resistant film with semi-conductive properties. A semi-conductive layer is formed between the braided shielding layer and the insulating interface, which can achieve the effect of reducing noise.

[0012] Further, the sheath layer is made of rubber material, and the rubber material includes the following raw materials in parts by weight: 100 parts of polyperfluoroethylene propylene resin, 35-45 parts of ABS resin, 30-40 parts of mica powder, 15-19 parts of fumed silica, 20-30 parts of magnesium hydroxide, 2-3 parts of flame retardant, 1-2 parts of vulcanizer, and 3-5 parts of heat stabilizer;

[0013] FEP resin can not only be continuously extruded into thin films in small sizes, but also has good wear resistance, softness, and resistance to high temperatures of 200°C. Acrylonitrile-butadiene-styrene copolymer (ABS) is a thermoplastic polymer material with high strength, good toughness, and easy processing.

[0014] Further, the flame retardant is prepared by the following steps:

[0015] S1, add cyanuric chloride and tetrahydrofuran to a four-necked flask with a mechanical stirring device, stir to dissolve and maintain the temperature of the system at 25 ° C, dissolve N-methyl propylene amine in an appropriate amount of tetrahydrofuran, and add it dropwise to the four-necked flask under stirring. After all the dropwise addition is completed, the reaction solution is heated to 50 ° C, and the reaction is continued at this temperature for 48 hours (the pH value is maintained at more than 10 with a NaOH solution with a concentration of 0.1 mol / L during the reaction). After the reaction is completed, most of the tetrahydrofuran solvent is removed by rotary evaporation, and then extracted with toluene 2-3 times, the organic phase is washed with a saturated NaCl aqueous solution 3-4 times, and then dried with anhydrous sodium sulfate, filtered, and concentrated under reduced pressure to obtain intermediate 1; the ratio of cyanuric chloride, tetrahydrofuran, and N-methyl propylene amine is 0.1 mol:150 mL:0.33 mol;

[0016] Cyanuric chloride reacts chemically with N-methylpropyleneamine to obtain intermediate 1. The specific reaction process is as follows:

[0017]

[0018] S2, add mercaptoethylamine and methanol aqueous solution (the volume ratio of methanol to distilled water is 10:1) to a four-necked flask with a stirring device, stir to dissolve and maintain the temperature of the system at 70°C, dissolve intermediate 1 and AIBN (azobisisobutyronitrile) in an appropriate amount of methanol, and add dropwise to the four-necked flask under stirring, react at 70°C for 4 hours, after the reaction is completed, cool to room temperature, filter, wash the filter cake with methanol and deionized water for 3-4 times respectively, and vacuum dry to obtain intermediate 2; the ratio of mercaptoethylamine, methanol aqueous solution, intermediate 1, and AIBN is 0.021mol:110mL:2.88g:0.22g;

[0019] Under the action of AIBN, the C=C on the intermediate 1 molecule undergoes a thiol-ene click reaction with the thiol on the mercaptoethylamine molecule. By controlling the molar ratio of the two to be close to 1:2, intermediate 2 is obtained. The reaction process is as follows:

[0020]

[0021] S3. Under N2 protection, p-carboxyphenylphosphonic acid, intermediate 2 and triethylamine are added to a dichloromethane solution containing DIC (N,N-diisopropylcarbodiimide), and the mixture is stirred and reacted for 3 hours at room temperature and under N2 protection. After the reaction, the solvent dichloromethane is removed by vacuum distillation, and n-hexane is added for recrystallization, filtered, and vacuum dried to obtain a flame retardant; the ratio of p-carboxyphenylphosphonic acid, intermediate 2, triethylamine, DIC and dichloromethane is 0.02 mol:4.43 g:2.02 g:1.26 g:150 mL;

[0022] Under the action of DIC and triethylamine, the -COOH on the p-carboxyphenylphosphonic acid molecule undergoes an amidation reaction with the -NH2 on the intermediate 2 molecule to generate a flame retardant. The reaction process is as follows:

[0023]

[0024] The flame retardant molecules obtained contain nitrogen-containing heterocycles, benzene rings, sulfur-containing groups and phosphoric acid groups. The nitrogen-containing heterocycles and benzene rings can form expanded carbon layers when exposed to fire or high temperature. The phosphoric acid groups can flame retard in the condensed phase and gas phase. The sulfur-containing groups can enhance the flame retardant effects of phosphorus and nitrogen, and exert excellent flame retardant effects in the condensed phase. Therefore, the flame retardant obtained is a highly efficient, multi-phase flame retardant component, and a small amount of addition can enable the material to obtain excellent flame retardant and fireproof effects. In addition, the flame retardant molecules also contain terminal C=C, which can participate in the copolymerization process during the melt mixing process with the matrix material, thereby improving the interaction between the flame retardant and the matrix, thereby improving the stability of the flame retardant, improving the migration resistance and exudation resistance of the flame retardant, and giving the sheath material a stable and lasting flame retardant effect.

[0025] Beneficial effects of the present invention:

[0026] The present invention adopts a high temperature resistant polytetrafluoroethylene film and a wrapping and sintering process to wrap the outer wall of the conductor to form an insulating layer. After wrapping and sintering, the polytetrafluoroethylene film can form a tight package with the conductor, making it difficult for the two to move relative to each other and separate, thereby reducing cable noise and making the cable more flexible. By adopting a semi-insulating polycrystalline silicon material as a semi-conductive glue, a semi-insulating polycrystalline silicon film is formed after solidification, which is a high temperature resistant film with semi-conductive characteristics. A semi-conductive layer is formed between the braided shielding layer and the insulating interface, which can achieve the effect of reducing noise.

[0027] The present invention adds magnesium hydroxide and a flame retardant to the outer sheath material at the same time. The flame retardant is a high-efficiency, multi-phase flame retardant component, and a small amount of addition can enable the material to obtain excellent flame retardant and fireproof effects. In addition, the flame retardant molecule also contains a terminal C=C, which can participate in the copolymerization process during the melt mixing process with the matrix material, thereby improving the interaction between the flame retardant and the matrix, thereby improving the stability of the flame retardant, improving the migration resistance and exudation resistance of the flame retardant, and giving the sheath material a stable and lasting flame retardant effect; thereby, the obtained cable meets the requirements of low noise and fire retardancy at the same time, and has broad application prospects. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] Preparation of flame retardant:

[0031] S1, 0.1 mol of cyanuric chloride and 150 mL of tetrahydrofuran were added to a four-necked flask with a mechanical stirring device, stirred to dissolve and the temperature of the system was maintained at 25°C, 0.33 mol of N-methylpropyleneamine was dissolved in an appropriate amount of tetrahydrofuran, and added dropwise to the four-necked flask under stirring. After all the additions were completed, the reaction solution was heated to 50°C and continued to react at this temperature for 48 hours (a 0.1 mol / L NaOH solution was used to maintain the pH value above 10 during the reaction). After the reaction was completed, most of the tetrahydrofuran solvent was removed by rotary evaporation, and then extracted with toluene twice, the organic phase was washed with a saturated NaCl aqueous solution three times, dried with anhydrous sodium sulfate, filtered, and concentrated under reduced pressure to obtain intermediate 1;

[0032] S2, add 0.021mol of mercaptoethylamine and 110mL of methanol aqueous solution (volume ratio of methanol to distilled water is 10:1) into a four-necked flask with a stirring device, stir to dissolve and maintain the temperature of the system at 70°C, dissolve 2.88g of intermediate 1 and 0.22g of AIBN (azobisisobutyronitrile) in an appropriate amount of methanol, and add dropwise into the four-necked flask under stirring, react at 70°C for 4h, and after the reaction is completed, cool to room temperature, filter, wash the filter cake with methanol and deionized water for 3 times respectively, and vacuum dry to obtain intermediate 2;

[0033] S3. Under N2 protection, add 0.02 mol of p-carboxyphenylphosphonic acid, 4.43 g of intermediate 2, and 2.02 g of triethylamine to 150 mL of dichloromethane solution containing 1.26 g of DIC (N,N-diisopropylcarbodiimide), and stir the reaction for 3 h at room temperature under N2 protection. After the reaction, remove the solvent dichloromethane by vacuum distillation, add n-hexane for recrystallization, filter, and vacuum dry to obtain a flame retardant.

[0034] Example 2

[0035] Preparation of flame retardant:

[0036] S1, 0.2 mol of cyanuric chloride and 300 mL of tetrahydrofuran were added to a four-necked flask with a mechanical stirring device, stirred to dissolve and the temperature of the system was maintained at 25°C, 0.66 mol of N-methylpropyleneamine was dissolved in an appropriate amount of tetrahydrofuran, and added dropwise to the four-necked flask under stirring. After all the additions were completed, the reaction solution was heated to 50°C and continued to react at this temperature for 48 hours (a 0.1 mol / L NaOH solution was used to maintain the pH value above 10 during the reaction). After the reaction was completed, most of the tetrahydrofuran solvent was removed by rotary evaporation, and then extracted with toluene 3 times, the organic phase was washed 4 times with a saturated NaCl aqueous solution, dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure to obtain intermediate 1;

[0037] S2, add 0.042 mol of mercaptoethylamine and 220 mL of methanol aqueous solution (the volume ratio of methanol to distilled water is 10:1) into a four-necked flask with a stirring device, stir to dissolve and maintain the temperature of the system at 70°C, dissolve 5.76 g of intermediate 1 and 0.44 g of AIBN (azobisisobutyronitrile) in an appropriate amount of methanol, and add dropwise into the four-necked flask under stirring, react at 70°C for 4 hours, and after the reaction is completed, cool to room temperature, filter, wash the filter cake with methanol and deionized water for 4 times respectively, and vacuum dry to obtain intermediate 2;

[0038] S3. Under N2 protection, add 0.04 mol of p-carboxyphenylphosphonic acid, 8.86 g of intermediate 2, and 4.04 g of triethylamine to 300 mL of dichloromethane solution containing 2.52 g of DIC (N,N-diisopropylcarbodiimide), and stir the reaction for 3 h at room temperature under N2 protection. After the reaction, remove the solvent dichloromethane by reduced pressure distillation, add n-hexane for recrystallization, filter, and vacuum dry to obtain a flame retardant.

[0039] Example 3

[0040] The sheath layer is made of rubber material, and the rubber material includes the following raw materials by weight: 100g of polyperfluoroethylene propylene resin, 35g of ABS resin, 30g of mica powder, 15g of fumed silica, 20g of magnesium hydroxide, 2g of the flame retardant prepared in Example 1, 1g of vulcanizing agent, and 3g of thermal stabilizer;

[0041] After the raw materials are mixed, they are put into an internal mixer for mixing for 20 minutes, and then vulcanized using a flat vulcanizer to obtain a rubber material.

[0042] Example 4

[0043] The sheath layer is made of rubber material, and the rubber material includes the following raw materials by weight: 100g of polyperfluoroethylene propylene resin, 40g of ABS resin, 35g of mica powder, 17g of fumed silica, 25g of magnesium hydroxide, 2.5g of the flame retardant prepared in Example 2, 1.5g of a vulcanizing agent, and 4g of a thermal stabilizer;

[0044] After mixing the raw materials, the raw materials were put into an internal mixer for mixing for 25 minutes, and then vulcanized using a flat vulcanizer to obtain a rubber material.

[0045] Example 5

[0046] The sheath layer is made of rubber material, and the rubber material includes the following raw materials by weight: 100g of polyperfluoroethylene propylene resin, 45g of ABS resin, 40g of mica powder, 19g of fumed silica, 30g of magnesium hydroxide, 3g of the flame retardant prepared in Example 1, 2g of vulcanizing agent, and 5g of thermal stabilizer;

[0047] After mixing the raw materials, the raw materials were put into an internal mixer for mixing for 30 minutes, and then vulcanized using a flat vulcanizer to obtain a rubber material.

[0048] The rubber materials obtained in Examples 3-5 were processed into standard test samples and subjected to the following performance tests:

[0049] Mechanical properties: electronic universal testing machine was used for testing and characterization (dumbbell-shaped standard specimen with a length of 50 mm, tensile test was performed at 200 mm / min);

[0050] Flame retardant performance: The oxygen index LOI of the material is tested using a digital oxygen index meter (sample size 100x6.5x3mm 3 ); UL-94 vertical burning rating was tested using a horizontal vertical burning tester (sample size was 100x13x3mm 3 );

[0051] The measured results are shown in the following table:

[0052] Example 3 Example 4 Example 5 Tensile strength / MPa 30.3 31.2 30.8 Elongation at break / % 1270 1355 1295 Oxygen index / % 31.2 31.6 31.5 UL-94 Rating V-0 V-0 V-0

[0053] It can be seen from the data in the above table that the rubber material prepared by the present invention has higher mechanical properties and excellent flame retardant properties.

[0054] Example 6

[0055] A low-noise flexible cable comprises a conductor, an insulating layer, a braided shielding layer and a sheath layer which are sequentially arranged from the inside to the outside;

[0056] The conductor is formed by twisting copper wires, the insulating layer is formed by wrapping and sintering a polytetrafluoroethylene film around the outer wall of the conductor, the surface of the insulating layer is coated with a semi-insulating polycrystalline silicon material, the braided shielding layer is coated on the outside of the insulating layer and is bonded to the outer wall of the insulating layer through the semi-insulating polycrystalline silicon material, and the sheath layer is coated on the outside of the braided shielding layer using the rubber material prepared in Example 3.

[0057] Example 7

[0058] A low-noise flexible cable comprises a conductor, an insulating layer, a braided shielding layer and a sheath layer which are sequentially arranged from the inside to the outside;

[0059] The conductor is made of twisted copper wires, the insulating layer is coated on the outer wall of the conductor by wrapping and sintering a polytetrafluoroethylene film, the surface of the insulating layer is coated with a semi-insulating polycrystalline silicon material, the braided shielding layer is coated on the outside of the insulating layer and is bonded to the outer wall of the insulating layer through the semi-insulating polycrystalline silicon material, and the sheath layer is coated on the outside of the braided shielding layer using the rubber material prepared in Example 4.

[0060] Example 8

[0061] A low-noise flexible cable comprises a conductor, an insulating layer, a braided shielding layer and a sheath layer which are sequentially arranged from the inside to the outside;

[0062] The conductor is made of twisted copper wires, the insulating layer is coated on the outer wall of the conductor by wrapping and sintering a polytetrafluoroethylene film, the surface of the insulating layer is coated with a semi-insulating polycrystalline silicon material, the braided shielding layer is coated on the outside of the insulating layer and is bonded to the outer wall of the insulating layer through the semi-insulating polycrystalline silicon material, and the sheath layer is coated on the outside of the braided shielding layer using the rubber material prepared in Example 5.

[0063] The cables of Examples 6-8 were subjected to a cable self-pulse signal test according to GB / T17737.1 standard (the lower the cable self-pulse signal, the lower the noise), and the results are shown in the following table:

[0064] Example 6 Example 7 Example 8 Self pulse signal / mV 0.82 0.77 0.79

[0065] It can be seen from the data in the above table that the cable obtained by the present invention has a low noise characteristic.

[0066] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0067] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A low-noise flexible cable, characterized in that: It includes a conductor, an insulating layer, a braided shielding layer and a sheath layer arranged in sequence from the inside to the outside, the conductor is made of twisted copper wires, the insulating layer is wrapped around the outer wall of the conductor by wrapping and sintering, the surface of the insulating layer is coated with semi-conductive glue, the braided shielding layer is wrapped around the outside of the insulating layer and adhered to the outer wall of the insulating layer through the semi-conductive glue, and the sheath layer is wrapped around the outside of the braided shielding layer; The sheath layer is made of rubber material, and the rubber material includes the following raw materials in parts by weight: 100 parts of polyperfluoroethylene propylene resin, 35-45 parts of ABS resin, 30-40 parts of mica powder, 15-19 parts of fumed silica, 20-30 parts of magnesium hydroxide, 2-3 parts of flame retardant, 1-2 parts of vulcanizer, and 3-5 parts of heat stabilizer; Wherein, the flame retardant is prepared by the following steps: S1, add cyanuric chloride and tetrahydrofuran to a four-necked flask with a mechanical stirring device, stir to dissolve and maintain the temperature of the system at 25 ° C, dissolve N-methyl propylene amine in an appropriate amount of tetrahydrofuran, and add it dropwise to the four-necked flask under stirring. After all the dropwise addition is completed, the reaction solution is heated to 50 ° C, and the reaction is continued at this temperature for 48 hours. After the reaction is completed, most of the tetrahydrofuran solvent is removed by rotary evaporation, and then extracted with toluene 2-3 times, the organic phase is washed with a saturated NaCl aqueous solution 3-4 times, and then dried with anhydrous sodium sulfate, filtered, and concentrated under reduced pressure to obtain intermediate 1; the ratio of cyanuric chloride, tetrahydrofuran, and N-methyl propylene amine is 0.1 mol:150mL:0.33 mol; S2, add mercaptoethylamine and methanol aqueous solution into a four-necked flask with a stirring device, stir to dissolve and maintain the temperature of the system at 70°C, dissolve intermediate 1 and AIBN in an appropriate amount of methanol, and add dropwise into the four-necked flask under stirring, react at 70°C for 4 hours, and after the reaction is completed, cool to room temperature, filter, wash the filter cake with methanol and deionized water for 3-4 times respectively, and vacuum dry to obtain intermediate 2; the ratio of mercaptoethylamine, methanol aqueous solution, intermediate 1, and AIBN is 0.021 mol:110 mL:2.88 g:0.22 g; S3. Under N2 protection, add p-carboxyphenylphosphonic acid, intermediate 2 and triethylamine to a dichloromethane solution containing DIC, and stir and react for 3 hours at room temperature and under N2 protection. After the reaction, remove the dichloromethane solvent by vacuum distillation, add n-hexane for recrystallization, filter, and vacuum dry to obtain a flame retardant; the ratio of p-carboxyphenylphosphonic acid, intermediate 2, triethylamine, DIC and dichloromethane is 0.02 mol:4.43 g:2.02 g:1.26 g:150 mL.

2. A low noise flexible cable according to claim 1, characterized in that: The insulating layer is made of polytetrafluoroethylene film.

3. A low noise flexible cable according to claim 1, characterized in that: The semi-conductive glue is made of semi-insulating polysilicon material.

4. A low noise flexible cable according to claim 1, characterized in that: During the reaction process of step S1, a NaOH solution with a concentration of 0.1 mol / L was used to maintain the pH value of the reaction solution above 10.

Citation Information

Patent Citations

  • Medium-voltage cross-linked polyethylene insulating power cable

    CN107674272A

  • Light low-noise cable

    CN108538460A